Effect Of Nutrient, Competitor Pests And Early Infestation On The Population Abundance Of Whitefly (Bemisia Tabaci Gennadius) On Brinjal (Solanum Melongena L.) - Zaini, Mohd Rasdi (2013)
The assemblage of these arthropods species (whitefly Bemisia tabaci Gennadius, aphids Myzus persicae Sulzer, thrips Thrips sp., red spider mites Tetranychus sp., and predatory mite Phytoseiulus sp.) on early infested (pre-infested) brinjal plants (Solanum melongena L.) that were fertilized with three levels of nutrients concentrations, N1 (50ppm=0.05g/L), N2 (150ppm=0.15g/L) and N3 (300ppm=0.3g/L) were investigated and the interactions of all trophic levels (pests, natural enemy and host plant) were evaluated. In addition, the infestation of whitefly was also closely associated with host plant phenology; vegetative and fruiting stages. Much higher whitefly infestation was recorded on non early-infestation (control) plants receiving high nutrient concentrations. However, on whitefly pre-infested plants, whitefly populations were lower regardless of the concentrations of nutrients supplied to the plants. The lowest infestation was observed on plants receiving 150 ppm nutrients, a rate recommended to the growers by the Department of Agriculture, Malaysia. Thus nutrient level was considered as the optimum nutrient concentration for sustaining whitefly infestation on brinjal plants. Furthermore, higher induction of plant chemical defence was detected at low whitefly population level which led to the conclusion that a more potent pest (whitefly) was able to stimulate the production of effective chemical defence.